POSSIBILITIES OF EARLY PREDICTION OF COMPLICATIONS OF PREECLAMPSIA (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The course and prognosis of preeclampsia in pregnant women is unpredictable; at the same time, the clinical picture may be “blurred” and nonspecific, a sudden development of a critical condition against the background of a stable course of the disease is possible The purpose. To determine the level of biochemical markers in preeclampsia in pregnant women and evaluate their impact on the development of obstetric and perinatal complications. Analyzed the state of 104 pregnant women with preeclampsia and their newborns. The control group was 31pregnant women without hypertensive disorders. Biochemical markers statistically significantly affects not only the health of pregnant women, but also the state of health of the newborn.